Electronic structure of multiferroic BiFeO3: Electron energy-loss spectroscopy and first-principles study. (May 2019) - Wang, S.; Xu, H.D.; Cai, J.; Wang, Y.P.; Tao, H.L.; Cui, Y.; He, M.; Song, B.; Zhang, Z.H.
Highlights: The individual interband transitions in BiFeO3 was assigned clearly. The hybridization of O 2p with Fe 3p presented in the DOS. The ferroelectricity originates from a strong O(2p)-Bi(6p) hybridization. The simulations of ELNES involved core-hole effects are more significant. Abstract: The electronic structure of BiFeO3 has been investigated by using electron energy loss spectrum and first-principle calculations. Assignments of the individual interband transitions have been accomplished by comparing the interband transition energy with the calculated PDOS. The DOS is mainly divided into two regions, the hybridized region of O 2p with Fe 3p in the valence band and that of O 2p hybridized with Bi 6p in the conduction band. From the simulation of high energy-loss near-edge structure, the core-hole effect is believed to be more significant. The feature groups for the experimental spectra of O K-edge and Fe L2, 3 -edge are consistent with simulation results.